Effects of Acute Lithium Treatment on Brain Levels of Inflammatory Mediators in Poststroke Rats. (27th September 2015) - Boyko, Matthew; Nassar, Ahmad; Kaplanski, Jacob; Zlotnik, Alexander; Sharon-Granit, Yael; Azab, Abed N.
Abstract : Stroke is a leading cause of mortality and morbidity worldwide. Few therapeutic options with proven efficacy are available for the treatment of this disabling disease. Lithium is the gold standard treatment for bipolar disorder. Moreover, lithium has been shown to exhibit neuroprotective effects and therapeutic efficacy as a treatment of other neurological disorders. This study was undertaken to examine the effects of lithium on brain inflammatory mediators levels, fever, and mortality in postischemic stroke rats. Ischemic stroke was induced by occlusion of the mid cerebral artery (MCAO). Pretreatment with a single dose of lithium at 2 hours before MCAO induction significantly reduced the elevation in interleukin- (IL-) 6 and prostaglandin E2 levels in brain of post-MCAO rats, as compared to vehicle-treated animals. On the other hand, lithium did not affect the elevation in IL-1 α, IL-10, IL-12, and tumor necrosis factor- α levels in brain of post-MCAO rats. Moreover, pretreatment with lithium did not alter post-MCAO fever and mortality. These results suggest that acute pretreatment with a single dose of lithium did not markedly affect post-MCAO morbidity and mortality in rats.